2022
DOI: 10.1089/ars.2021.0091
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Instability in Mammalian Cells

Abstract: Significance: The small, multicopy mitochondrial genome (mtDNA) is essential for efficient energy production, as alterations in its coding information or a decrease in its copy number disrupt mitochondrial ATP synthesis. However, the mitochondrial replication machinery encounters numerous challenges that may limit its ability to duplicate this important genome and that jeopardize mtDNA stability, including various lesions in the DNA template, topological stress and an insufficient nucleotide supply.Recent Adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 209 publications
(341 reference statements)
0
9
0
Order By: Relevance
“…For clinical applications that target mtDNA disorder, it is essential to achieve homoplasmic status in a cell by eliminating the mutated mtDNA. In contrast to nuclear DNA (nDNA) repair pathways, the efficient DNA double-strand break (DSB) repair and homologous recombination (HR) mechanisms are lacking in mammalian mitochondria ( Nissanka et al, 2019 ; Carvalho et al, 2021 ). Once cut on both strands, mtDNA molecules are not repaired, which results in rapid degradation of mtDNA in mammalian cells ( Peeva et al, 2018 ).…”
Section: Current Methods For Mitochondrial Genome Editingmentioning
confidence: 99%
“…For clinical applications that target mtDNA disorder, it is essential to achieve homoplasmic status in a cell by eliminating the mutated mtDNA. In contrast to nuclear DNA (nDNA) repair pathways, the efficient DNA double-strand break (DSB) repair and homologous recombination (HR) mechanisms are lacking in mammalian mitochondria ( Nissanka et al, 2019 ; Carvalho et al, 2021 ). Once cut on both strands, mtDNA molecules are not repaired, which results in rapid degradation of mtDNA in mammalian cells ( Peeva et al, 2018 ).…”
Section: Current Methods For Mitochondrial Genome Editingmentioning
confidence: 99%
“…In essence, depending on the burden of damage present within mitochondria, DNA polymerase γ can either facilitate the retention of healthy mtDNA or further aggrandize mito-dysfunction ( 69 ). Importantly, regardless of the cause of mtDNA damage, damaged mtDNA that escapes from the mitochondria into the cytosol can activate inflammatory responses, via TLR9, cGas-STING, and NLRP3 inflammasome signaling ( 70 , 71 ). Chronic activation of these cellular responses contributes to the sterile inflammation seen in aging ( 70 ).…”
Section: Mitochondrial Dna (Mtdna) Damage Accumulationmentioning
confidence: 99%
“…The presence of MMR proteins has been reported in mammalian mitochondria, but the activity of this pathway remains elu- Mitochondrial DNA (mtDNA) is also damaged by the direct and indirect action of radiation and it undergoes repair, although mtDNA repair mechanisms are less characterized. Evidence has shown that BER activity, carried out by the same proteins active in the nucleus, is also predominant in mitochondria to repair oxidized bases and AP sites [62]. Mammalian mitochondria also contain proteins for nucleotide excision repair (NER), the NHEJ and HR repair pathways, but the repair activities of these pathways are not clearly demonstrated and are still under investigation.…”
Section: Repair Of Dna Damage Originated In the Space Environmentmentioning
confidence: 99%